METHODOLOGY OF GRAPHIC COMPETENCE DEVELOPMENT OF FUTURE ENGINEERS BASED ON AN INNOVATIVE APPROACH - Akbarov Adhamjon; Yo’ldashev Bilol; Nurmatov Sardor (American Journals Publishing, 2022)
This article talks about the development of graphic competence based on an innovative approach, the use of effective methods of computer graphics, geometric modeling of objects.
Keywords: material-technical, scientific potential, OpenGL, trajectory